2019
DOI: 10.1088/1742-6596/1235/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Improving One-Time Pad Algorithm on Shamir’s Three-Pass Protocol Scheme by Using RSA and ElGamal Algorithms

Abstract: This study aims to cover the shortcomings of the one-time pad algorithm used in the Shamir’s three-pass protocol scheme. In this study, the technique used to cover the weakness of one-time pad algorithm is by changing each ciphertext generated from the three paths in the three pass protocol scheme. Ciphertext modification is performed by encrypting the cipher-text by using the RSA and Elgamal algorithms to generate super ciphertext. The first line and the third line are encrypted by using the RSA algorithm and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Sidik et al [9] suggested a technique in the one-time pad (OTP) manner's flaw that can be concealed by altering each cipher text in the three pathways used in the threepasses protocol method. To modify the cipher text, a combination of the ElGamal and RSA algorithms is employed to generate super cipher text.…”
Section: Literature Review On Commerce Transaction Requests Encryptionmentioning
confidence: 99%
“…Sidik et al [9] suggested a technique in the one-time pad (OTP) manner's flaw that can be concealed by altering each cipher text in the three pathways used in the threepasses protocol method. To modify the cipher text, a combination of the ElGamal and RSA algorithms is employed to generate super cipher text.…”
Section: Literature Review On Commerce Transaction Requests Encryptionmentioning
confidence: 99%
“…Problem increases when the third party obtains all three messages that enables the password to be cracked by using simple exclusive addition. OTP in TPP has been modified by using various encryption techniques such as H-Rabin [16], Hill Cipher [17], Viginere Cipher [18] and El-Gamal [19]. TPP modification can also be made for single or multiple links of TPP message transfer [20].…”
Section: Introductionmentioning
confidence: 99%